Impacts of health communication on HIV/AIDS prevention on adolescents in Katsina State, Nigeria - Isyaku, Sagir Lawan (Direct Research Journal of Social Science and Educational Studies, 2024)
HIV/AIDS is a disease that currently receives global concern by both international, governmental and non-governmental organizations and individuals owing to its devastating socio economic implications especially on youths. Several policies and Programmes were initiated and implemented and some currently ran to curtail its spread. Knowledge and awareness of the disease is among the measures identified as key to checking its spread. Health communication targets educating people on some important health issues with a view to arming them with information required to redirect their behaviour and actions towards improved health status. This study is aimed at investigating the role of health communication strategies in curtailing the spread of HIV/AIDS among adolescents in the state. Using Qualitative Survey method (via Focus Group Discussion and in-depth Interview), the study randomly selected three Local Governments each from the three Senatorial Districts of Katsina, Daura and Funtua and Interviewed staff of the Katsina State Agency for the Control of AIDS. It discovered that Health Communication strategies has succeeded in making people become aware of the disease and the information has significantly impacted on the people’s attitude towards adopting measures that could minimize the spread of the virus. It therefore recommended use of other non-media method like town hall meetings and market day sensitizations among others.